2006
DOI: 10.1152/ajpregu.00086.2006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of corticotropin-releasing factor and CRF receptors in micturition pathways after cyclophosphamide-induced cystitis

Abstract: ticotropin-releasing factor (CRF) is a prominent neuropeptide involved in micturition reflexes, and different roles in these reflexes have been suggested. These studies examined the expression of CRF in the urinary bladder and lumbosacral sacral parasympathetic nucleus (SPN) in response to cyclophosphamide (CYP)-induced cystitis (4 h, 48 h, or chronic) in rats. The expression of CRF receptors, CRF 1 and CRF2, was examined in urinary bladder from control and CYP-treated rats. Urinary bladder and lumbosacral spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 66 publications
4
64
1
1
Order By: Relevance
“…4B). These cells show a similar morphology to mast cells and macrophages previously described in the urinary bladder after CYP-induced cystitis (20,26). Double-labeling experiments demonstrated that these pERK-IR cells expressed the CD86 antigen (e.g., macrophages, dendritic cells) (Fig.…”
Section: Perk Expression In Urinary Bladder Nerve Fibers After Cyp Trsupporting
confidence: 77%
See 1 more Smart Citation
“…4B). These cells show a similar morphology to mast cells and macrophages previously described in the urinary bladder after CYP-induced cystitis (20,26). Double-labeling experiments demonstrated that these pERK-IR cells expressed the CD86 antigen (e.g., macrophages, dendritic cells) (Fig.…”
Section: Perk Expression In Urinary Bladder Nerve Fibers After Cyp Trsupporting
confidence: 77%
“…Cy3 was visualized with a filter with an excitation range of 560 -596 nm and an emission range from 610 -655 nm. Grayscale images acquired in tiff format here imported into MetaMorph image analysis software (version 4.5r4; Universal Imaging, Downingtown, PA) as previously described (26,58). Images were calibrated for pixel size by applying a previously created calibration file to convert all measurements from pixels to square micrometers.…”
Section: Assessment Of Positively Stained Urinary Bladder Regionsmentioning
confidence: 99%
“…Other brain circuits in which CRF is prominent have not been directly associated with bladder regulation. Moreover, it is unlikely that the site of action of NBI-30775 is at the level of the bladder because neither CRF 1 receptor nor CRF 1 immunoreactivity are present in bladder (19). The finding that NBI-30775 prevented the urodynamic consequences of social stress without affecting CRF upregulation in Barrington's nucleus neurons indicates that it was acting at the level of the spinal cord where Barrington's nucleus neurons terminate so that the social stress-induced bladder dysfunction failed to occur in spite of elevated levels of CRF in this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the bladder, CRF is abundantly expressed in areas involved in the control of micturition (i.e., Barrington's nucleus, lumbosacral areas of the spinal cord) and administration of various CRF receptor agonists and antagonists alters cystometric parameters [38,39,40]. Following stress or bladder inflammation, increases in CRF-IR and/or CRF2 receptor expression have been detected in these areas and in the bladder itself [41,42]. These converging lines of evidence implicate the CRF system as a potential mediator of stress-induced bladder hyperalgesia as well.…”
Section: Discussionmentioning
confidence: 99%